Lignocellulosic Composites Prepared Utilizing Aqueous Alkaline/Urea Solutions with Cold Temperatures - Brent Tisserat; Zengshe Liu; Luke M. Haverhals (International Journal of Polymer Science)
Lignocellulosic composites (LCs) were fabricated by partially dissolving cotton to create a matrix that was reinforced with osage orange wood (OOW) particles and/or blue agave fibers (AF). LCs were composed of 15–35% cotton matrix and 65–85% OWW/AF reinforcement. The matrix was produced by soaking cotton wool in a cold aqueous alkaline/urea solvent and was stirred for 15 minutes at 350 rpm to create a viscous gel. The gel was then reinforced with lignocellulosic components, mixed, and then pressed into a panel mold. LC panels were soaked in water to remove the aqueous solvent and then oven dried to obtain the final LC product. Several factors involved in the preparation of these LCs were examined including reaction temperatures (−5 to −15°C), matrix concentration (15–35% cotton), aqueous solvent volume (45–105 ml/panel), and the effectiveness of employing various aqueous solvent formulations. The mechanical properties of LCs were determined and reported. Conversion of the cotton into a suitable viscous gel was critical in order to obtain LCs that exhibited high mechanical properties. LCs with the highest mechanical properties were obtained when the cotton wools were subjected to a 4.6% LiOH/15% urea solvent at −12.5°C using an aqueous solvent volume of 60 ml/panel. Cotton wool subjected to excessive cold alkaline solvents volumes resulted in irreversible cellulose breakdown and a resultant LC that exhibited poor mechanical properties.